Foreign Shocks, Monetary Policy, and Macroeconomic Fluctuations in a Small Open Economy: A SVAR Study of Malaysia - Zulkefly, Abdul Karim; Bakri, Abdul Karim (Acta Universitatis Danubius, 2016)
This paper investigates the effect of foreign shocks upon domestic macroeconomic fluctuations and monetary policy, and examines the effectiveness of domestic monetary policy as a stabilization policy in Malaysia. Monetary policy variables (interest rate and money supply) have been measured through a non-recursive structural VAR (SVAR) identification scheme, which allows the monetary authority to set the interest rate and money supply after observing the current value of foreign variables, domestic output and inflation. The results show the important role of foreign shocks in influencing Malaysian monetary policy and macroeconomic variables. There is a real effect of monetary policy, that is, a positive shock in money supply increases domestic output. In contrast, a positive interest rates shock has a negative effect on domestic output growth and inflation. The effects of money supply and interest rate shocks on the exchange rate and stock prices are also consistent with standard economic theory. In addition, domestic monetary policy is able to mitigate the negative effect of external shocks upon domestic economy.